Optical Burst Switching Network With Nolm As Buffering-Switching Device - Roger, Tang Mun Fai (2007)
In this research project, nonlinear optical loop mirror (NOLM) and the loop buffer are integrated to provide an efficient buffering-switching device. In order to obtain an optimum performance for the proposed device, various limitations are studied and analyzed. Among the deficiencies evaluated are various types of noises that cause intensity fluctuation on the buffered and demultiplexed signals. Switching characteristics of the NOLM demultiplexer are so analyzed.